Effect of Conservation Agriculture on the Growth and Productivity of Wheat (Triticum Spp.) Crop (Damascus University Journal of agriculture sciences, 2024)
A field experiment was conducted in AboJarash farm-faculty of agriculture- Damascus university, during the growing seasons (2021/2022), in order to evaluate the performance of  bread wheat cultivar (Douma-6) and durum wheat variety (Douma-1) under conservation agriculture (CA) comparing with conventional tillage system (CT) in rotation with  vetch  crop. The experiment was carried out according to randomized complete block design with split plots arrangement in three replicates.Results showed significant differences between the two agricultural systems (Conservation and conventional tillage systems), where CA surpassed significantly in plant height, plant leaf area index,number of spikes per unit land area, 1000-kernel weight(g) , number of grains/m2, and grain yield.The total number of spikes.m-2, number of grains.m-2, 1000 kernel weight, grain yield were significantly the highest under CA-system (416.33 spikes. m-2 , 14682.33 grains.m-2, 46.50 g, 4641.66 kg.ha-1 respectively) comparing with CT-system (295.6 spikes. m-2 , 11005.10 grains.m-2, 36.80 g, 4025.00 kg.ha-1 respectively). The variety of bread wheat Douma-6 recorded significantly the highest mean value of the traits number of spikes.m-2, number of grains.m-2 and grain yield (394.50 spikes.m-2, 13762.78 grains.m-2 and 4483.33 kg.ha-1 respectively) comparing with durum wheat variety Douma-1 (317.33 spikes.m-2, 11924.65 grains.m-2 and 4183.33 kg.ha-1 respectively). Whereas the durum wheat variety Douma-1recorded significantly the highest mean value of 1000 kernel weight (47.49 g) compared with bread wheat variety Douma-6 (35.83 g). We conclude from this study to apply conservation agriculture system in order to improve the productivity of wheat crop under rainfed conditions.
Keywords: Conservation Agriculture (CA); Conventional Tillage (CT) Wheat; Growth Traits; Grain Yield